Dampak Insentif Pajak Perumahan Terhadap Potensi Penerimaan Pajak Negara Dan Peningkatan Pendapatan Masyarakat : Kasus Provinsi Papua - Irawan, Towaf Totok (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2016)
Until now the government and private sector have not been able to address the backlog of 13.5 million housing units for ownership status and 7.6 million units for residential status. The high price of land has led to the high price of the house so that low-income communities (MBR) is not able to reach out to make a home purchase. In addition to the high price of land, tax factors also contribute to the high price of the house. The government plans to issue a policy for the provision of tax incentives, ie abolish VAT on home-forming material transaction. This policy is expected to house prices become cheaper, so the demand for housing increases, and encourage the relevant sectors to intensify its role in the construction of houses. It is expected to replace the lost tax potential and increase incomes. Analysis of the impact of tax incentives housing to potential state revenue and an increase in people's income, especially in Papua province is using the table IO because in addition to looking at the role each sector can also see the impact on taxes (income tax 21 Pph 25 Pph, VAT), and incomes (wage). Although in the short-term impact is still small, but very rewarding in the long run. Keywords: Backlog, Gross Input, Primary Input, Intermediate Input